The impact of cardiovascular disease risk factors, inflammation and the vasculature on diastolic function in rheumatoid arthritis - Mokotedi, Lebogang.Palesa (My University, 2020)
Cardiovascular disease (CVD) is a major cause of mortality in patients with rheumatoid arthritis (RA). In RA, heart failure contributes to the increased CVD mortality rates and is most often characterised by diastolic dysfunction and a normal ejection fraction. High-grade systemic inflammation and its related adverse traditional cardiovascular risk factors contribute to CVD in RA. However, the relative contribution of traditional risk factors and inflammation to diastolic dysfunction in RA is uncertain. Furthermore, the mechanisms whereby chronic systemic inflammation impairs diastolic function are currently under investigation. This thesis compromise of a series of human and animal studies designed to advance our understanding of the direct and indirect role of systemic inflammation in the development of diastolic dysfunction. Recently the criteria for the classification of diastolic dysfunction have been revised. In the first study, I compared the estimated prevalence and potential determinants of left ventricular (LV) diastolic dysfunction upon applying different (previous versus current) classification criteria in 176 RA patients who met the American College of Rheumatology/European League against Rheumatism criteria for RA. I found that the waist-to-hip ratio was independently associated with impaired LV relaxation as indexed by the early-to-late diastolic filling velocity ratio (E/A) and the lateral early diastolic mitral annular velocity (e’). Low diastolic blood pressure was independently associated with increased LV filling pressures as indexed by E/e’. The estimated prevalence of diastolic dysfunction was markedly lower upon application of the current criteria (22%) compared to previous (59%) criteria (p<0.0001). Moreover, one SD increase in waist-to-hip ratio was associated with diastolic dysfunction when applying the new criteria (OR=2.61 (95% CI=1.51–4.52), p=0.0006), whereas one SD increase in diastolic blood pressure was inversely associated with diastolic dysfunction when using previous criteria (OR=0.57 (95% CI=0.40–0.81), p=0.002). These data therefore suggest that central adiposity and low diastolic blood pressure are independently associated with diastolic function in patients with RA. Further, the application of different criteria markedly alters the prevalence and associated risk factors of diastolic dysfunction in RA. Although there is an association between chronic inflammation and diastolic dysfunction in cross-sectional studies, there is currently no direct evidence to support the role of high-grade inflammation mediating changes in cardiac function in experimental models of RA. In the second study, I assessed the role of high-grade inflammation on LV diastolic and systolic function in collagen-induced arthritis (CIA) rats (an experimental model most similar to RA). Systolic function was determined using conventional, two-dimensional echocardiography and Speckle Tracking Echocardiography. Compared to controls (n=12), CIA (n=21) rats had impaired LV relaxation as indexed by reduced lateral e’ and e’/a’ (early- iv to-late diastolic mitral annular myocardial velocity) and increased filling pressures as indexed by E/e’. Although there were no differences in ejection fraction and LV endocardial fractional shortening between the groups, LV global radial strain (p<0.0001), circumferential strain (p=0.01), global strain rate (p=0.0003) and circumferential strain rate (p=0.001) were reduced in CIA compared to controls. Higher concentrations of tumor necrosis factor alpha (TNF-α), interleukin 6 (IL-6), interleukin 1β (IL-1β) and C-reactive protein (CRP) were associated with reduced lateral e’, e’/a’, LV global radial and circumferential strain and strain rate. This study showed that exposure to high-grade inflammation directly affects LV diastolic function and myocardial deformation without causing contractile changes. In RA, endothelial dysfunction is central to the development of atherosclerosis. Recently, altered microvascular endothelial changes have been proposed as the link between exposure to inflammation and diastolic dysfunction. In the third study, I determined the effect of high-grade inflammation on vascular function in CIA rats. Vascular function was measured using vascular reactivity in the mesenteric and saphenous arteries and circulating biomarkers of vascular function including vascular adhesion molecules (VCAM-1) and asymmetric dimethylarginine (ADMA) of rats exposed to inflammation (n=21) for 10 weeks and controls (n=12). Circulating inflammatory markers including TNF-α, IL-6, IL-1β and CRP were elevated in CIA compared to controls (all p<0.00001). Acetylcholine-induced relaxation was impaired in mesenteric arteries of CIA compared to controls (p=0.01). VCAM-1 was higher in CIA compared to controls (p=0.02); ADMA was similar in both groups. TNF-α, IL-6, IL-1β and CRP were significantly related to VCAM-1. VCAM-1 was associated with impaired maximal relaxation (Emax) induced by acetylcholine in mesenteric arteries. Circulating ADMA was not associated with inflammatory markers or acetylcholine-induced relaxation in mesenteric arteries. This study showed that circulating VCAM-1 may be a key mediator of inflammation-induced endothelial dysfunction in arthritic rats. Inflammation impairs vascular function and RA patients experience increased arterial stiffness. In non-RA populations, arterial function is related to diastolic function. Hence, I evaluated the potential impact of impaired arterial function on diastolic function in patients with RA. Arterial function was measured with applanation tonometry in 173 RA patients. The timing of the reflected wave was associated with E/A (partial r=0.17, p=0.03) and arterial stiffness as indexed by carotid-femoral pulse wave velocity (PWV) was related to increased E/e’ (partial r=0.19, p=0.02). The timing of the reflected wave, forward wave magnitude and pulse pressure amplification were associated with impaired relaxation (E/A <0.8). PWV was related to increased left ventricular filling pressure (E/e’ >12). The timing of the reflected wave (OR=0.66 (95% CI=0.47-0.92), p=0.002) and PWV (OR=1.86 (95% CI=1.20-2.90, p=0.006) were related to diastolic dysfunction according to previous criteria; timing of the forward wave (OR=1.71 (95% CI=1.11-2.66, p=0.03) was associated with diastolic v dysfunction according to recent criteria. Taken together, this study showed that early wave reflection and arterial stiffness are associated with LV impaired relaxation and increased filling pressure, respectively, in RA. In addition, different classification criteria set markedly impact the associations of arterial function measures with estimated diastolic dysfunction in RA. In conclusion, the findings reported in this thesis advance our understanding of the mechanisms whereby CVD risk is increased in conditions characterised by high-grade inflammation. Evidence is provided that traditional risk factors are strongly related to diastolic dysfunction in RA. Additionally, this thesis provides evidence that exposure to systemic inflammation impairs left ventricular diastolic function and causes early alterations in myocardial systolic function, not reflected in changes in myocardial contraction. Furthermore, inflammation impairs vascular function via endothelial activation. Arterial function is independently related to diastolic function in patients with RA. Impaired arterial function may therefore link cardiovascular risk factor exposure to CVD outcomes in patients with RA
A thesis submitted to the Faculty of Health Sciences, University of the Witwatersrand, in fulfillment of the requirements for the degree of Doctor of Philosophy Johannesburg, South Africa, 2019